Estudo da formação do inflamassoma durante a infecção por Plasmodium: implicações na patogênese da malária - Marco Antônio Ataíde Silva (2014)
Plasmodium infection causes about 600,000 deaths annually. Several studies related to the pathogenesis of malaria indicate that this is a highly inflammatory disease, and the clinical manifestations are close related to the overproduction of proinflammatory mediators during the erythrocytic stage of Plasmodium life cycle. It was demonstrated that P. chabaudi infection promotes the formation of the multiprotein platform known as inflammasome, and consequently activation of caspase-1, which is responsible for the maturation of the IL-1β, a pyrogenic cytokine. This event is dependent on TLR9 / MyD88 signaling, and expression of P2X7, IFN-γ, ASC, NLRP3 and / or NLRP12. Wild type mice infected with P. chabaudi become hypersensitive to LPS or to co-infection with S. typhimurium, secreting high levels of IL-1β, and succumbing within a few hours later. However, a treatment using an IL-1 receptor antagonist increased the resistance of these animals to LPS-induced shock or to bacterial co-infection. It is important to point that mice deficient in molecules involved in the inflammasome assembly, as ASC, NLRP3, NLRP12 and Casp-1 were also less susceptible to shock induced by LPS. Finally, it has also been found active caspase-1 within monocytes from patients infected with P. vivax, and oligomers of ASC, NLRP3 and NLRP12, indicating a possible involvement of these elements in the formation of the inflammasome during malaria. Thus, we conclude that the infection by Plasmodium is sufficient to provide signals for inflammasome assembly and caspase-1 activation. In addition, this phenomenon is highly deleterious to the hosts, if they are exposed to microbial stimuli, as a TLR agonist, capable to induce the expression of pro-IL-1β. Therefore, once episodes of co-infection between Plasmodium and Gram-negative bacteria are very common, caspase-1 activation during malaria must be considered a severity factor.